Penerapan Sistem E-Filling Sebagai Tolok Ukur Kepatuhan Wajib Pajak Dalam Penyampaian SPT Tahunan - Putri, Lutfi Zunaida; Sari, Shinta Permata (Transpublika Publisher, 2025)
Taxpayer compliance is very important to achieve tax revenue targets. The Directorate General of Taxes uses E-Filling to make taxpayers more independent and active in fulfilling their tax obligations and increase taxpayer compliance. The aim of this research is to identify the use of e-filling as a measure of taxpayer compliance in submitting Annual Tax Returns and the effect of implementing this system on individual taxpayer compliance in submitting Annual Tax Returns with seven constructs in the Unified Theory of Acceptance and Use of Technology 2 model ( UTAUT 2): performance expectations, effort expectations, social factors, facilitating conditions, pleasure motivation, price value, habits, and adding interest variables using the e-filling system to analyze whether e-filling can increase taxpayer compliance. The research method uses a quantitative approach with primary data from questionnaire responses. This research was conducted with a sample of 206 taxpayers at KPP Pratama Sukoharjo. The results of the research are that performance expectations, pleasure motivation, and habits influence interest in using the e-filling system, while the variables of business expectations, social influence, facilitating conditions, and price value do not influence interest in using the e-filling system. Furthermore, facilitating conditions have no effect on individual taxpayer compliance in submitting Annual Tax Returns, while habits and interest in using the e-filling system influence individual taxpayer compliance in submitting Annual Tax Returns.